2013
DOI: 10.1016/j.drugalcdep.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reinforcer magnitude and nicotine amount on smoking's acute reinforcement enhancing effects

Abstract: Background Nicotine’s acute effects on enhancing reinforcement from sensory rewards, shown in animal models, appear to occur with smoking in humans. These effects may vary due to reinforcer magnitude and amount of acute smoke intake (dose). Methods In a fully within-subjects design, dependent smokers (n=23) participated in 3 sessions. Each session followed overnight abstinence and involved 4 trials to assess responding via progressive ratio (PR50%) for sensory reinforcement from high, moderate, or low prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 26 publications
9
40
0
Order By: Relevance
“…The former results are very consistent with, but the latter is contrary to, our prior studies of nicotine from cigarette smoking, which consistently showed enhancement of music reinforcement (Perkins and Karelitz, 2013a, 2013b, 2014), as in the ad lib smoking session of the current study (see Fig. 1).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The former results are very consistent with, but the latter is contrary to, our prior studies of nicotine from cigarette smoking, which consistently showed enhancement of music reinforcement (Perkins and Karelitz, 2013a, 2013b, 2014), as in the ad lib smoking session of the current study (see Fig. 1).…”
Section: Discussionsupporting
confidence: 80%
“…Recent human studies have confirmed animal models showing acute effects of nicotine in enhancing reinforcement from rewards made available independent of nicotine intake (Perkins and Karelitz, 2013a, 2013b, 2014). However, nicotine dosing in this human research was manipulated via controlled tobacco smoking, and we are not aware of any human research examining reinforcement enhancing effects of nicotine administered via non-tobacco means.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Satisfaction is generally one of the stronger effects found when nicotine is compared to placebo. 54,55 Given that nicotine is increasingly recognized as a secondary, rather than a primary reinforcer, [56][57][58][59] it may be that the unique flavorings associated with e-cigarettes are leading to the increased reports of satisfaction.…”
Section: E-cigarettes Versus Cigarettesmentioning
confidence: 99%